The Soul of the Camera - DuChemin, David (Rocky Nook, 2017)
As both an art form and a universal language, the photograph has an extraordinary ability to connect and communicate with others. But with over one trillion photos taken each year, why do so few of them truly connect? Why do so few of them grab our emotions or our imaginations? It is not because the images lack focus or proper exposure; with advances in technology, the camera does that so well these days. Photographer David duChemin believes the majority of our images fall short because they lack soul. And without soul, the images have no ability to resonate with others. They simply cannot connect with the viewer, or even--if we're being truthful--with ourselves. In The Soul of the Camera: The Photographer's Place in Picture-Making, David explores what it means to make better photographs. Illustrated with a collection of beautiful black-and-white images, the book's essays address topics such as craft, mastery, vision, audience, discipline, story, and authenticity. The Soul of the Camera is a personal and deeply pragmatic book that quietly yet forcefully challenges the idea that our cameras, lenses, and settings are anything more than dumb and mute tools. It is the photographer, not the camera, that can and must learn to make better photographs--photographs that convey our vision, connect with others, and, at their core, contain our humanity. The Soul of the Camera helps us do that.